2002
DOI: 10.1002/gps.510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuropsychiatric symptoms of Alzheimer's disease on Chinese and American caregivers

Abstract: The results were surprising, in that American and Chinese (Taipei and Hong Kong) caregivers exhibited similar distress or lack of distress in response to delusions, hallucinations, agitation, anxiety, euphoria, disinhibition, irritability, aberrant motor behavior, sleep and appetite symptoms of Alzheimer's disease patients. Chinese caregivers were less affected by depression and apathy in patients with Alzheimer's disease than Caucasian caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 24 publications
6
35
1
4
Order By: Relevance
“…Also, this is one of the few trials that have studied the effects of MBSR on mental health in the Chinese population. Several studies have shown that caregivers in Hong Kong endure levels of stress and burden comparable to their counterparts in Western countries [44,45]. The characteristics of participants in our study were similar to those of the previous studies, i.e.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Also, this is one of the few trials that have studied the effects of MBSR on mental health in the Chinese population. Several studies have shown that caregivers in Hong Kong endure levels of stress and burden comparable to their counterparts in Western countries [44,45]. The characteristics of participants in our study were similar to those of the previous studies, i.e.…”
Section: Discussionsupporting
confidence: 78%
“…The characteristics of participants in our study were similar to those of the previous studies, i.e. mainly females with a secondary or lower education level and a low income [45,46,47]. …”
Section: Discussionsupporting
confidence: 69%
“…Chinese cultural values also tend to put greater emphasis on relational harmony over individual achievement, and thus may have contributed to greater tolerance to memory-related problems but less so to disruptive behaviors, especially those which cause embarrassment (Ikels, 1998(Ikels, , 2002. Previous studies have compared the effect of different problem behaviors on caregiving costs (e.g., burdens, depression) in different cultures (e.g., Pang et al, 2002). Less of such cross-cultural comparisons have been conducted with positive caregiving appraisals.…”
Section: Criteria-related Validitymentioning
confidence: 96%
“…Psychotic symptoms in dementia are variable, but can be persistent, with lasting symptoms present in 39-62% after 3 months and 43-57% after 1 year (Schneider and Dagerman, 2004). Psychotic symptoms impair functional ability (Schneider et al, 2003), increase risk for the occurrence of affective distress (including anxiety, phobias, and depression) (Brodaty et al, 2001;Schneider et al, 2003), and predict earlier institutionalization (González-Salvador et al, 1999;Lopez et al, 1999;Pang et al, 2002) in patients with dementia.…”
Section: Introductionmentioning
confidence: 98%